2011
DOI: 10.1188/11.cjon.41-48
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Patient Navigation Program

Abstract: This study examined the value and effectiveness of a patient navigation program in terms of timeliness of access to cancer care, resolution of barriers, and satisfaction in 55 patients over a six-month period. Although not statistically significant, the time interval between diagnostic biopsy to first consultation with a cancer specialist after program implementation was reduced from an average of 14.6 days to 12.8 days. The time interval between diagnostic biopsy to initiation of cancer treatment also was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 36 publications
1
82
0
5
Order By: Relevance
“…Weber [13] also found no benefit in treatment adherence, but did find some benefit in post-treatment monitoring. Studies by Haideri [14], Ell [15] and Koh [16] also showed minimal to no benefit on timeliness to cancer treatment. Other studies, however, have shown benefit.…”
Section: Patient Navigation In Cancer Carementioning
confidence: 99%
“…Weber [13] also found no benefit in treatment adherence, but did find some benefit in post-treatment monitoring. Studies by Haideri [14], Ell [15] and Koh [16] also showed minimal to no benefit on timeliness to cancer treatment. Other studies, however, have shown benefit.…”
Section: Patient Navigation In Cancer Carementioning
confidence: 99%
“…67 These navigators are either peers or educated professionals who assist patients in moving through the health care process. Koh et al 68 studied the use of a patient navigation system in cancer patients. Their study showed that more than 71% of the barriers to care such as fear, lack of financial resources, transportation, and child care were resolved at the first treatment visit thanks to interventions by patient navigators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ce changement exige des infirmiĂšres en oncologie qu'elles continuent de saisir les occasions qui s'offrent Ă  elles et de crĂ©er des stratĂ©-gies innovatrices pour assurer aux patientes un parcours sans heurts tout au long de la trajectoire de soins (Case, 2010). Les Ă©tudes montrent que la prĂ©sence d'infirmiĂšres pivots en oncologie produit des rĂ©sultats mesurables et que cette prĂ©sence devrait ĂȘtre Ă©valuĂ©e afin que soient examinĂ©es l'efficacitĂ© et la valeur des interventions infirmiĂšres qui utilisent de maniĂšre optimale leurs connaissances et compĂ©tences spĂ©cialisĂ©es pour le bien des patientes (Case, 2010;Koh, Nelson et Cook, 2010). Les donnĂ©es indiquent que les femmes qui reçoivent un diagnostic de cancer du sein et le traitement associĂ© considĂšrent important que les prestataires de soins transmettent de l'information claire et cohĂ©rente pour les soutenir tout au long de leur expĂ©rience (Grunfeld et Earle, 2010;Mayer, Gerstel, Leak et Smith, 2012;.…”
Section: Plus De 90 % Des Participantes Avaient Compris L'informatiunclassified
“…La rĂ©duction des effets psychosociaux liĂ©s au diagnostic de cancer aide les patientes Ă  acquĂ©-rir des habiletĂ©s d'adaptation, ce qui peut amĂ©liorer l'issue du traitement et la qualitĂ© de vie (Hryniuk, Simpson, McGowan et Carter, 2014;Institute of Medicine, 2008). Les cliniques ont conçu et Ă©valuĂ© avec efficacitĂ© des programmes d'infirmiĂšres pivots pour combler les lacunes au niveau des besoins psychosociaux des familles et en matiĂšre d'information et de coordination des soins offerts aux patientes admises au centre de traitement du cancer (Horner, Ludman, McCorkle, Canfield, Flaherty et al, 2012;Koh, Nelson et Cook, 2010).…”
Section: Plus De 90 % Des Participantes Avaient Compris L'informatiunclassified